Ready Made Garment (RMG) factories during the pandemic: aapping the effects in Bangladesh - Shajahan, Sadril; Islam, Md. Faizul; Choudhury, Afshana; Chowdhury, Fahim S (Palgrave Macmillan, 2024)
Since the start of Covid-19 Pandemic in Bangladesh, policies were steered and stimulus packages were provided by the Government for the Ready Made Garments (RMG) industry which contributes heavily on the country’s economy through exports and employment generation of millions of workers but was struggling due to pandemic triggered supply chain disruption and order cancellation from global buyers. It can be a crucial exploration to know how RMG factories fought back after reopening from one month closure during the initial stage of the Covid-19 Pandemic in Bangladesh in 2020. This analysis is a contribution to such exploration by making a comparison based on the data of export oriented RMG factories in Bangladesh from two rapid surveys conducted in two phases in 2020 for understanding the effects of the pandemic on the Bangladesh RMG sector. While factories covered by the rapid surveys were sampled from the database of the ‘Mapped in Bangladesh’ project, the comparison of this analysis addressed several important factors including operational status, capacity utilization and workers employed during Pandemic.